Concrete Mix Design Using Particle Packing Method: Literature Review, Analysis, and Computation - Shreya Sunil Tolmatti; Sanskruti Jaywant Jadhav; Sakshi Satish Jadhav; Mayur M. Maske (Universitas Komputer Indonesia, 2021)
Particle packing technology is used to reduce the amount of cement in concrete by optimizing the concrete mix, resulting in more sustainable concrete. In this study, four different methods were used to determine the distribution of the mixture presented; packing density method, packing density method, IS code method, and packing density method. In the packing density method, the paste content that exceeds the voids will increase along with the increase in the quality of the concrete. In cases of packing density, the cement-water ratio decreases with the quality of the concrete. In the packing of too many trials, trials and tribulations should be carried out to achieve the ratio of water-cement and paste content for a certain grade of concrete. This correlation curve helps reduce the experiments involved in determining the ratio of semen and paste content for a given concrete quality. The water and cement contents for the packing density and the IS code method are almost the same for each particular concrete class. The workability of concrete achieved was more in the packing density method than the IS code method for the same concrete quality, because the water-cement ratio was slightly higher in the packing density method than the IS code method. The required fine aggregate particles are more in terms of packing density method compared to the IS code method. Therefore, more water and cement are required in terms of packing density. The correlation curve can be used to determine the ratio of water-cement and paste the content that exceeds the voids for a certain concrete quality